IMF Staff papers : Volume 25 No. 2. (IMF Staff Papers; IMF Staff Papers ;, 1978)
This paper outlines the Asian currency market provides an intermediation function between several Asian countries and the Eurocurrency market. However, soon after its creation in 1968, the Asian market went beyond this function and has now developed a substantial regional network of financial transactions. The Asian currency market was developed when the economy of Singapore was going through an important period of transition that was caused by the independence of the island in the mid-1960s and by a rapid phasing out of large British military installations. In addition to an important effort of economic development at home, this period of transition has involved expanding financial and trade relations to countries other than the British Commonwealth and the immediate neighbors. Several factors contributed to the establishment of the Asian currency market in Singapore. In the 1960s, the rapid economic growth of a number of Asian countries, an increased flow of direct investment, and a greater participation of multinational corporations in the economy of Asia generated a growing pool of foreign currencies in the hands of the private sector.